An update on cell intrinsic negative regulators of the NLRP3 inflammasome. Issue 6 (26th January 2018) - Poudel, Barun; Gurung, Prajwal
Abstract: Inflammasomes are multimeric protein complexes that promote inflammation (through specific cleavage and production of bioactive IL‐1β and IL‐18) and pyroptotic cell death. The central role of inflammasomes in combating infection and maintaining homeostasis has been studied extensively. Although inflammasome‐mediated inflammation and cell death are vital to limit pathogenic insults and to promote wound healing/tissue regeneration, unchecked/uncontrolled inflammation, and cell death can cause cytokine storm, tissue damage, autoinflammatory and autoimmune diseases, and even death in the afflicted individuals. NLRP3 is one of the major cytosolic sensors that assemble an inflammasome. Given the adverse consequences of uncontrolled inflammasome activation, our immune system has developed tiered mechanisms to inhibit NLRP3 inflammasome activation. In this review, we highlight and discuss recent advances and our current understanding of mechanisms by which NLRP3 inflammasome can be negatively regulated. Abstract : Review on recent advances in our understanding of the mechanisms that negatively regulate NLRP3 inflammasome activation.